Spatio-temporal pattern of land degradation from 1990 to 2015 in Mongolia - Wang, Juanle; Wei, Haishuo; Cheng, Kai; Ochir, Altansukh; Davaasuren, Davaadorj; Li, Pengfei; Shun Chan, Faith Ka; Nasanbat, Elbegjargal (Elsevier B.V., 2020)
Land degradation is an important environmental problem facing the world. "Land Degradation Neutrality" is one of the core indicators in the 15th goal of the "United Nations Sustainable Development Goals" for 2030. Mongolia is an important country for global land degradation. The increasingly serious land degradation has caused a direct impact on the ecosystem of the entire Mongolian plateau. We analyzed the patterns of land degradation and restoration during 1990-2010 and 2010-2015 and determined the driving forces behind the variations, by using fine resolution land cover data for the first time in Mongolia. The results showed that the spatial distribution of newly increased land degradation and restoration have a strong transitional nature. For the past 25 years, the trend of land change in Mongolia was dominated by land degradation. However, land degradation was accompanied by ongoing restoration of some land areas, and the capacity for land restoration has been gradually improved. This study discovers a series of typical land degradation and restoration regions and provides an interpretation of the driving forces in these areas. The joint effects of natural and socioeconomic factors have been found to result in land degradation and restoration in different regions.